(Co‐)Oligomerization of Olefins to Hydrocarbon Fuels: Influence of Feed Composition and Pressure. Issue 5 (14th March 2023) - Fuchs, Constantin; Arnold, Ulrich; Sauer, Jörg
Abstract: The co‐oligomerization of methanol‐based C2‐4 olefins on a heterogeneous nickel silica‐alumina catalyst enables the production of fuel‐range hydrocarbons. The objective of this study was the production of gasoline and jet fuel, which was achieved with an overall selectivity of above 90 %. The influence of olefin feed composition and pressure was investigated at 120 °C. By employing olefin mixtures instead of one single olefin, selectivity to specific chain lengths decreases and quantities of the individual products converge. An increase of olefin pressure from 16 to 32 bar slightly shifts the liquid products to shorter oligomers and raises feed conversion. Abstract : In the context of renewable fuels, this study addresses the synthesis of paraffinic gasoline and jet fuel from C2‐4 olefins, which may be supplied via methanol. Different olefin feed mixtures were investigated at varying partial pressures to gain insights into the oligomerization reaction network, product distribution and molecular branching.